Erectile Dysfunction in Hypertension and Cardiovascular Disease : A Guide for Clinicians - Viigimaa, Margus; Vlachopoulos, Charalambos; Doumas, Michael (Springer International Publishing : Imprint: Springer, 2015)
This concise guide to the often overlooked association between erectile dysfunction and hypertension/cardiovascular disease covers a wide range of aspects of importance to the clinician. It examines the impact of antihypertensive drug therapy on erectile function and explains how the management of erectile dysfunction in hypertensive patients depends on a variety of factors. Different treatment approaches are described, including lifestyle modification, PDE-5 inhibitors and other novel agents, and behavioral therapy, and helpful therapeutic algorithms are presented. A further focus of the book is the potential role of erectile dysfunction as an early diagnostic indicator of asymptomatic coronary artery disease and a prognostic marker for cardiovascular events. In addition, key background information is supplied on epidemiology and pathophysiology, and the significance of erectile dysfunction in different patient groups, such as the elderly and those with chronic kidney disease, is examined. Erectile dysfunction is a major public health problem affecting more than ten percent of the general male population and is now considered to be predominantly of vascular origin. This book will be informative and of practical value for all practitioners responsible for caring for the very many patients who experience erectile dysfunction in the setting of hypertension and cardiovascular disease.